BUDAYA KEPEMIMPINAN PENDIDIKAN SEBAGAI FAKTOR PENENTU DALAM MANAJEMEN KEARSIPAN - Asmahan Rifa Salma; Indri Nur’Aini; Nurzein Ismail; Retno Setio Ning Asih; Siswadi (STKIP Subang, 2026)
This study aims to analyze the role of educational leadership culture as a determining factor in archival management. Effective leadership culture is believed to create a well-organized, systematic, and sustainable archival management system. This research employs a qualitative approach using conceptual analysis through a review of relevant literature. The findings indicate that leadership culture characterized by vision, discipline, and good governance orientation has a significant influence on the effectiveness of archival management. Leaders with strong awareness of the importance of archives tend to foster structured archival systems, enhance accountability, and facilitate information access. Conversely, weak leadership culture leads to poor archival management practices. Therefore, strengthening educational leadership culture is essential to optimize archival management in educational institutions. Keywords: leadership culture, educational leadership, archival management, records management